MANGUPA DITINJAU DARI PERSPEKTIF HUKUM ISLAM - Aripin, Musa (IAIN Padangsidimpuan, 2018)
Mangupa ceremony or wages is one of the traditional ceremonies originating from the Southern Part of Tapanuli (Tabagsel) of North Sumatra province, this ceremony aims to return the tondi (spirit) to the body and ask for blessings from God Almighty to always be safe, healthy, and cheap sustenance in life. The effort to summon this tondi agency is done by serving a set of pangupa materials and pangupa advice which is systematically compiled and carried out by various parties consisting of parents, kings, and other traditional parties.This is often disputed in modern society today, there are some who think that this kind of action is an act of polytheism, but some others think that this custom does not fall into shirk. So from here, the author tries to analyze in depth about the legal status of this mangupa from the perspective of Islamic law that the writer will peel in the discussion below.